Mastering your fellowship - Mergan Naidoo; Klaus von Pressentin; Tasleem Ras; Ts'epo Motsohi (South African Family Practice)
The series, ‘Mastering your Fellowship’, provides examples of the question format encountered in the written and clinical examinations, Part A of the Fellowship of the College of Family Physicians of South Africa (FCFP SA) examination. The series is aimed at helping family medicine registrars to prepare for this examination.